Post-Conflict Security Sector and Public Finance Management : Lessons from Afghanistan - Middlebrook, Peter; Simpson, Rima; Melloul, Karene (World Bank, Washington, DC, 2012)
In recent years, international organizations have concluded that standard principles of Public Finance Management (PFM) are equally applicable to all areas of the national budget, including the security sector. In many cases long-term external assistance may be required for the security sector, generating severe trade-offs with other priority sectors which also require long-term external support. Overcoming the legacy of a fiscally unsustainable and poorly managed security sector calls for full application of PFM principles to support the establishment of checks and balances required to establish a wholly accountable security sector. The recent World Bank PFM review of Afghanistan, perhaps the first example of such a review, provides a number of lessons, summarized in this note. Some of these include: security in post-conflict situations is a key condition for a return to political normalcy and conversely, development is also needed for security; PFM practices can take into consideration the most complex and confidential issues without undermining the application of the fundamental principles of accountability to elected civil authorities; and reviewing security reform through a PFM lens reduces risks and costs to both the country concerned and donors.